Metaphor in The Folklore Album by Taylor Swift : A Semantics Study - Keazia Yasmina Frida; Ida Zuraida (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
This research aims to identify the types of metaphors and analyze the meaning of the metaphor in the song lyrics of the “Folklore” album by Taylor Swift. The method used in this research is the descriptive qualitative research method. The data used are taken from the song lyrics of the “Folklore” album by Taylor Swift. The data are gathered by listening and reading, identifying, categorizing, analyzing the lyrics of the songs, and finally, drawing conclusions. The theory employed in this study is the theory of metaphors as proposed by Lakoff and Johnson (1980), while the approach to the meaning of metaphors is based on Hurford and Heasley (1983). The results show 35 words containing metaphors found in 8 song lyrics in the “Folklore” album by Taylor Swift. There are three types of meanings of metaphors, namely, 13 data of structural metaphors (38%), 12 data of orientational metaphors (35%), and 10 data of ontological metaphors (27%). In terms of meaning, denotative meaning, connotative meaning, and affective meaning are found in the song lyrics.